The Outcome of Obesity in Pregnancy: A Cross-Sectional Study - Muzaffar, Tabassum; Abbas, Sana; Sheraz, Shahida; Bano, Islam; Sohail, Amina; Wasim, Zahra (Pakistan Armed Forces Medical Journal, 2023)
Objective: To find out fetal and maternal outcomes among obese pregnant females.Study Design: Cross-sectional study.Place and Duration of Study: Department of Gynaecology and Obstetrics, Combined Military Hospital Rawalpindi, from Jun 2020 to Jun 2021.Methodology: A total of 124 pregnant obese women (BMI more than 30kg/m2), gestational age between 13-24 months, having fasting blood glucose and blood pressure within normal limits were enrolled in the study and were subsequently followed throughout pregnancy upon antenatal visits scheduled as per guidelines. Participants with diabetes mellitus or hypertension,above 40 years of age, family or previous history of gestational diabetes, and pre-eclampsia were also excluded from the study. Fetal and maternal outcomes were noted.Results: One hundred and twenty-four (124) pregnant obese women were enrolled in the study with a mean age of 33.7±4.1 years (21 -38 years). Out of which, 86(69.4%) had cesarean section primarily due to pre-eclampsia, prolonged or dysfunctional labour causing fetal distress. There were 8 cases of miscarriage and 3 cases of stillbirth. 26(21.0%) women presented with gestational diabetes mellitus, 31(25.0%) with pre-eclampsia and 12(9.7%) developed both conditions. There were 7(5.6%) participants who delivered babies with macrosomia, 1(0.8%) anencephaly, 3(2.4%) congenital deafness and 1(0.8%) cleft lip.Conclusion: Obesity in pregnancy can lead to serious maternal and fetal outcomes ranging from abortions to neonatal anomalies and fetal death. A high index of suspicion is required to diagnose and manage these difficult conditions.